The Gender Role Attitude Scale (GRAS) as an alternative for the crisis in measurement of attitudes towards gender roles in Latin America: A study in Chilean university students - Pérez Sánchez, Beatriz; Concha-Salgado, Andrés; Fernández-Suárez, Asunción; Juarros-Basterretxea, Joel; Rodríguez-Díaz, Francisco Javier (Anales de Psicología / Annals of Psychology, 2021)
We have experienced sociocultural changes, which have favoured the development of egalitarian gender role attitudes (GRA). Nevertheless, the revolution in gender roles is incomplete, and the lack of equity in social structures limits the individual experiences in equality. In the face of this reality, the scientific community is demanding a modernised system for measuring GRA. We present adaptation, evidence of factorial and convergent validity, accuracy, ceiling and floor effect, norms of interpretation by sex, and analyses of the GRA easiest or most difficult to modify, for the Gender Role Attitudes Scale (GRAS) in a sample of 1013 Chilean university students. The GRAS has a two-factor structure that allows the evaluation of stereotyped and transcendent attitudes of gender roles in family, social, and work contexts. The scale presents convergent validity with a sexual double standard measure and is more reliable in the low scores of transcendence and the high scores of stereotyped attitudes. Transcendent factor had a ceiling effect, and stereotyped attitudes had a floor effect. Family gender roles are the easiest to change, and work-related roles the most difficult. The authors discuss the need for a structural change to reactivate the revolution of gender roles in Chile.